Revolutionizing Combinatorial Mathematics: Cutting-Edge Summation Methods and Advanced Permutation Strategies for Complex Problem Solving - Samanta, Santu (Journal of Educational Research and Policies, 2025)
Permutation is the Mathematical technique of arrangement. This paper is the study based on the summation of the numbers which is arranged some digits may be in all distinct or some of digits same. The formula provides a more efficient and structured method for computing summations in permutation, reducing complexity and improving computational efficiency. This study contributes to mathematical problem-solving by offering a new perspective on structured summation in permutation-based calculations.